Isolated Tuberculosis of Pancreas – A rare entity & A Diagnostic Dilemna - Dr. Vinamra Mittal; Dr. Shikhar Mishra; Dr. Varun Aggarwal; Dr. Neha Bansal; Dr. Ankit Jain; Dr. Mohit Goyal; Dr. A.Sayana (Innovative Journal of Medical and Health Sciences, 2022)
First described by Auerbach in 1944, Pancreatic Tuberculosis constitutes one of the rarest presentations of abdominal Tuberculosis. Most of the semi micsaneo plastic lesion involving the body or head, but a careful and thorough examination along with FNAC can aide in making an accurateiagnos is. Literature search revealed that only nine cases of Pancreatic Tuberculos is have been reported from India in last 5years. Here we present a rare case of an Isolated Pancreatic Tuberculosis diagnosed on Cytology and treated successfully by anti-tubercular drugs thus preventing major surgery.